Protective Effects of 10-nitro-oleic Acid in a Hypoxia-Induced Murine Model of Pulmonary Hypertension - Klinke, Anna (American Thoracic Society, 2014)
Pulmonary arterial hypertension (PAH) is characterized by adverse remodeling of pulmonary arteries. Although the origin of the disease and its underlying pathophysiology remain incompletely understood, inflammation has been identified as a central mediator of disease progression. Oxidative inflammatory conditions support the formation of electrophilic fatty acid nitroalkene derivatives, which exert potent anti-inflammatory effects. The current study investigated the role of 10-nitro-oleic acid (OA-NO(2)) in modulating the pathophysiology of PAH in mice. Mice were kept for 28 days under normoxic or hypoxic conditions, and OA-NO(2) was infused subcutaneously. Right ventricular systolic pressure (RVPsys) was determined, and right ventricular and lung tissue was analyzed. The effect of OA-NO(2) on cultured pulmonary artery smooth muscle cells (PASMCs) and macrophages was also investigated. Changes in RVPsys revealed increased pulmonary hypertension in mice on hypoxia, which was significantly decreased by OA-NO(2) administration. Right ventricular hypertrophy and fibrosis were also attenuated by OA-NO(2) treatment. The infiltration of macrophages and the generation of reactive oxygen species were elevated in lung tissue of mice on hypoxia and were diminished by OA-NO(2) treatment. Moreover, OA-NO(2) decreased superoxide production of activated macrophages and PASMCs in vitro. Vascular structural remodeling was also limited by OA-NO(2). In support of these findings, proliferation and activation of extracellular signal-regulated kinases 1/2 in cultured PASMCs was less pronounced on application of OA-NO(2).Our results show that the oleic acid nitroalkene derivative OA-NO(2) attenuates hypoxia-induced pulmonary hypertension in mice. Thus, OA-NO(2) represents a potential therapeutic agent for the treatment of PAH.